Plasma progesterone concentration in beef heifers receiving exogenous glucose, insulin, or bovine somatotropin - Cooke, Reinaldo Fernandes [UNESP]; Cappellozza, B. I.; Reis, M. M. [UNESP]; Bohnert, D. W.; Vasconcelos, José Luiz Moraes [UNESP] (Amer Soc Animal Science, 2012)
Three experiments were conducted to evaluate plasma concentrations of glucose, insulin, IGF-I, and progesterone (P4) in pubertal beef heifers receiving exogenous glucose, insulin, or sometribove zinc. All heifers used had no luteal P4 synthesis but received a controlled internal drug-releasing device containing 1.38 g of P4 to estimate treatment effects on hepatic P4 degradation. In Exp. 1, 8 pubertal, nulliparous Angus x Hereford heifers (initial BW = 442 +/- 14 kg; initial age = 656 +/- 7 d) were randomly assigned to receive, in a crossover design containing 2 periods of 10 h, intravenous (i.v.) infusions (10 mL) of insulin (1 mu g/kg of BW; INS) or saline (0.9%; SAL). Treatments were administered via jugular venipuncture in 7 applications (0.15 mu g insulin/kg BW per application) 45 min apart (from 0 to 270 min). Blood samples were collected immediately before each infusion as well as at -120, -60, 330, 390, and 450 min relative to the first infusion. Heifers receiving INS had greater (P < 0.01) plasma insulin, reduced (P <= 0.04) plasma glucose and IGF-I, and similar (P = 0.62) plasma P4 concentrations compared with SAL heifers. In Exp. 2, the same heifers were assigned to receive, in a similar experimental design as Exp. 1, i.v. infusions (10 mL) of 1) insulin (1 mu g/kg BW) and glucose (0.5 g/kg BW; INS+G) or 2) SAL. Heifers receiving INS+G had greater (P <= 0.02) plasma insulin, glucose, and P4 but reduced (P = 0.01) plasma IGF-I concentrations compared with SAL heifers. In Exp. 3, the same heifers were assigned to receive, in a crossover design containing 2 periods of 14 d, subcutaneous (s.c.) injections of 1) 250 mg of sometribove zinc (BST) or 2) SAL. Blood samples were collected 3 h apart (0900, 1200, 1500, and 1800 h) from heifers on d 6, 8, and 10 relative to treatment administration (d 1). Heifers receiving BST had greater (P < 0.01) plasma glucose and IGF-I and similar (P >= 0.67) plasma insulin and P4 concentrations compared with SAL heifers. Results from this series of experiments suggested that concurrent increases in glucose and insulin are required to reduce hepatic catabolism and increase plasma concentrations of P4 in bovine females.
Keywords: beef heifers; glucose; insulin; insulin-like growth factor-I; progesterone